Proteome Analysis of Condensed Barley Mitotic Chromosomes - Perutka, Zdeněk; Kaduchová, Kateřina; Chamrád, Ivo; Beinhauer, Jana; Lenobel, René; Petrovská, Beáta; Bergougnoux, Véronique; Vrána, Jan; Pecinka, Ales; Doležel, Jaroslav; Šebela, Marek (Frontiers in Plant Science, 2021)
Proteins play a major role in the three-dimensional organization of nuclear genome and its function. While histones arrange DNA into a nucleosome fiber, other proteins contribute to higher-order chromatin structures in interphase nuclei, and mitotic/meiotic chromosomes. Despite the key role of proteins in maintaining genome integrity and transferring hereditary information to daughter cells and progenies, the knowledge about their function remains fragmentary. This is particularly true for the proteins of condensed chromosomes and, in particular, chromosomes of plants. Here we purified barley mitotic metaphase chromosomes by a flow cytometric sorting and characterized their proteins. Peptides from tryptic protein digests were fractionated either on a cation exchanger or reversed-phase microgradient system before liquid chromatography coupled to tandem mass spectrometry. Chromosomal proteins comprising almost 900 identifications were classified based on a combination of software prediction, available database localization information, sequence homology, and domain representation. A biological context evaluation indicated the presence of several groups of abundant proteins including histones, topoisomerase 2, PARP2, condensin subunits, and many proteins with chromatin-related functions. Proteins involved in processes related to DNA replication, transcription and repair as well as nucleolar proteins were found. We have experimentally validated the presence of FIBRILLARIN 1, one of the nucleolar proteins, on metaphase chromosomes, suggesting that plant chromosomes are coated with proteins during mitosis, similar to those of human and animals. These results improve significantly the knowledge of plant chromosomal proteins and provide a basis for their functional characterization and comparative phylogenetic analyses.